2012
DOI: 10.1039/c2nr12053d
|View full text |Cite
|
Sign up to set email alerts
|

Microwave-assisted synthesis of gold nanoparticles self-assembled into self-supported superstructures

Abstract: Passivated gold nanoparticles were synthesized through a microwave-assisted process in a two-phase system, in the presence of 1-dodecanethiol. An average particle size of 1.8 nm of the gold nanoparticles obtained and 0.35 S.D. was determined through HRTEM and STEM analysis. It was observed that these nanoparticles spontaneously self-assemble into self-supported superstructures of 1 μm in diameter avg and 400 nm thickness, yielding an off-white powder which can be handled as a simple powder. XRD analysis indica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
38
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 48 publications
(90 reference statements)
2
38
0
Order By: Relevance
“…The HRTEM result of CAO-AuNPs (Figure 5D) not only showed a clear ellipsoidal shape, but also displayed the distribution of the lattice of AuNPs that was consistent with the FCC structure of gold [10,20,31], which indicated that the obtained AuNPs are crystal structures. The zeta potential (ZP) of CAO-AuNPs was determined to be −20 mV, indicating that the CAO-AuNPs had a high negatively charged surface, which could be beneficial for the delivery of positively charged drugs [2,35].…”
Section: Resultssupporting
confidence: 61%
“…The HRTEM result of CAO-AuNPs (Figure 5D) not only showed a clear ellipsoidal shape, but also displayed the distribution of the lattice of AuNPs that was consistent with the FCC structure of gold [10,20,31], which indicated that the obtained AuNPs are crystal structures. The zeta potential (ZP) of CAO-AuNPs was determined to be −20 mV, indicating that the CAO-AuNPs had a high negatively charged surface, which could be beneficial for the delivery of positively charged drugs [2,35].…”
Section: Resultssupporting
confidence: 61%
“…Tetrachloroauric acid (HAuCl 4 · 3H 2 O ≥99.9 % ) was purchased from Sigma Aldrich and used without further purification. Au NPs were synthesized according to a previously reported method with some modifications . Nucleation of small NPs (∼ 0.7–1.3 nm) was induced in an ETHOS EZ microwave digestion system with a microwave frequency of 2.5 GHz.…”
Section: Methodsmentioning
confidence: 99%
“…[30,31] Microwave irradiation method was embraced to synthesize AuNPs by using citric acid as a reducing agent and cetyltrimethyl ammonium bromide (CTAB) as a binding agent. [32] In addition, other utilized physical technique such as ultrasonic waves, laser ablation, solvothermal method and electrochemical methods are available in literature for synthesis of AuNPs.…”
Section: World Journal Of Pharmaceutical Researchmentioning
confidence: 99%